Bio-geotechnologies for mine site rehabilitation - Prasad, M. N. V. (Majeti Narasimha Vara), 1953-; Favas, Paulo Jorge de Campos; Maiti, Subodh Kumar (Elsevier, 2018)
Bio-Geotechnologies for Mine Site Rehabilitation deals with the biological, physical, chemical, and engineering approaches necessary for the reclamation of mine waste. As mining has negative effects on natural resources and deteriorates the quality of the surrounding environment, this book provides coverage across different types of mining industries, which are currently creating industrial deserts overloaded with technogenic waste. The book offers cost-effective strategies and approaches for contaminated sites, along with remediation and rehabilitation methods for contaminated soils and waste dumps. It is an essential resource for students and academics, but is also ideal for applied professionals in environmental geology, mineral geologists, biotechnologists and policymakers.